Some glad morning : poems - Crooker, Barbara, 1945- (University of Pittsburgh Press, 2019)
Some Glad Morning, Barbara Crooker's ninth book of poetry, teeters between joy and despair, faith and doubt, the disconnect between lived experience and the written word. Primarily a lyric poet, Crooker is in love with the beauty and mystery of the natural world, even as she recognizes its fragility. But she is also a poet unafraid to write about the consequences of our politics, the great divide. She writes as well about art, with ekphrastic poems on paintings by Hopper, O'Keeffe, Renoir, Matisse, Cezanne, and others. Many of the poems are elegaic in tone, an older writer tallying up her losses. Her work embodies Bruce Springsteen's dictum, "it ain't no sin to be glad we're alive," as she celebrates the explosion of spring peonies, chocolate mousse, a good martini, hummingbirds' flashy metallics, the pewter light of September, Darryl Dawkins (late NBA star), saltine crackers. While she recognizes it might all be about to slip away, "Remember that nothing is ever lost," she writes, and somehow, we do.